Geneza, budowa i ważniejsze rozwiązania ustawy o ochronie wynalazków, wzorów i znaków towarowych z dnia 5 lutego 1924 roku - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In the article the historical conditions for the enactment of the first Polish law on the protection of inventions, trade marks and designs in the Second Republic of Poland, taking into account the ongoing legislative work in the parliamentary forum, were explained in detail.Moreover, the structure of the above mentioned Act was presented and attention was drawn to the more important legal solutions contained in the Act, in terms of its structure.
Keywords: własność intelektualna; własność przemysłowa; ochrona wynalazków, znaków towarowych i wzorów; prawo II Rzeczpospolitej